Analisis Proses Legislasi Undang-Undang Republik Indonesia Nomor 3 Tahun 2022 Tentang Ibu Kota Negara Perspektif Maslahah Mursalah - Dewi Ulfa Lailatul Fitria; Fathur Rochim (Bahasa Indonesia, 2025)
This study analyzes the legislative process of the Republic of Indonesia Law Number 3 of 2022 concerning the State Capital (IKN) from the perspective of maslahah mursalah. Maslahah mursalah is a concept in Islamic law referring to public interest not explicitly mentioned in sacred texts but considered essential for societal welfare. The study evaluates whether the legislative process of the IKN Law has considered the principles of maslahah mursalah, including public participation, transparency, and social justice. The analysis reveals that although the objective of relocating the capital to alleviate Jakarta's burden and promote equitable development aligns with the concept of maslahah, the legislative process of the IKN Law was perceived as hasty and lacked optimal public participation. This raises questions about the extent to which the principles of maslahah mursalah were applied in the legislative process.